ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF MYRISTICA FATUA VAR. MAGNIFICA (BEDDOME) SINCLAIR - Mr, Viveka; ChandraShekar kr (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To evaluate the antioxidant and antibacterial activities of different extracts of Myristica fatua. Methods: Antioxidant potential of different extracts of M. fatua was analyzed by following 2, 2-diphenyl -1-picryl hydrazyl and reducing power assay. Extracts were also screened against two Gram-positive and three Gram-negative bacteria. The minimum inhibitory concentration of the extracts was determined by macrodilution technique and the minimum bactericidal concentration (MBC) values by subculturing method. Phenolics and flavonoids were determined by standard procedures. An attempt was made to analyze the correlation between antibacterial and antioxidant activity with phenols and flavonoids using Pearson’s correlation. Results: Bark hexane extract showed the significantly high amount of phenolics 195 (gallic acid equivalent[GAE]/mg), whereas testa methanolic extract showed significantly highest flavonoids (332 mg quercetin equivalent [QE]/g). Ethyl acetate extracts of testa and methanolic extracts of kernel and aril exhibited a better antioxidant activity in terms of IC values. The MBC assay revealed that chloroform extract of aril at the concentration of 5 mg/ml was enough to inhibit the growth of bacteria Staphylococcus aureus. Flavonoids were moderately correlated with reducing power. 50 Conclusion: Our study suggests that the possibility of using the aril and seed extracts as a natural food preservative and other parts as a new source of natural antioxidants for pharmaceutical industries. Keywords: Myristica fatua var. magnifica, Flavonoids, Phenolics, Antioxidant, Antibacterial.